Analisis Cluster: Pedagogy Knowledge Guru Menuju Digitalisasi Pendidikan di Era Merdeka Belajar Berdasarkan Daerah Afirmasi - Ratnaya, I Gede; Hajiriah, Titi Laily; Fajri, Siti Rabiatul; Fitriani, Herdiyana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The competence possessed by teachers is an important factor in achieving learning and education goals in schools. One of the essential competencies in the learning process is pedagogical competence. The Era of Independent Learning marks a paradigm shift in education in Indonesia by utilizing technology to improve the quality of learning. However, challenges arise especially in affirmation areas that have different socio-economic conditions and educational infrastructure. This study aims to determine the ability of teachers' pedagogic competence in facing the digitalization of education in the era of Independent Learning based on affirmation areas. In addition, this study also groups teachers based on their pedagogic abilities towards the digitalization of education in the era of Freedom of Learning using cluster analysis analyzed through SPSS For Windows 23. The research sample consisted of 100 respondents from several affirmation regions in Indonesia, such as Bima, West Lombok, East Lombok, Central Lombok, Maluku, NTT, Papua, and Sumbawa. Additional respondents came from non-affirmative areas as comparators, including Mataram City, Surabaya, Kalimantan, and Magetan East Java. The results of the study show that West Lombok Regency has the highest level of pedagogic competence among affirmation areas with a score of 87.74, while Bima Regency has the lowest score of 75. This average score is still categorized as high because it is above 75. The comparison area shows that Magetan has the highest average score of 100. Cluster analysis showed the formation of two groups, namely cluster 1 consisting of teachers from Magetan, Papua, West Lombok, and NTT, and cluster 2 consisting of teachers from Kalimantan, Bima, Surabaya, Mataram City, Maluku, Sumbawa, and Central Lombok.